Potensi Ampas Kopi sebagai Bahan Pembuatan Sabun Batang untuk Meningkatkan Ekonomi Rumah Tangga di Desa Sarirogo - Budi Prabowo; Achmad Abiyyu Yusuf Sinatrya J; Adelia Putri Sumarsono; Greace Inri Apulina Br Sinulingga; M. Hadziqul Afkar (Jurnal Informasi Pengabdian Masyarakat, 2024)
This outreach program aims to empower the community of Sarirogo Village in managing household waste by utilizing coffee grounds to create valuable products, specifically solid soap. The community service activities include training in the production of solid soap from coffee grounds, production assistance, and raising awareness about the importance of organic waste management. Through these activities, the residents of Sarirogo Village are provided with knowledge and skills in the environmentally friendly process of making solid soap. Additionally, the program aims to increase awareness about the importance of household waste management and to support sustainable living practices. It is hoped that through this community service program, the people of Sarirogo Village can reduce household waste and acquire new skills that can enhance their well-being.